Adoption of agricultural technologies in the semi-arid northern Ethiopia: A Panel Data Analysis - Menasbo Gebru; Stein T. Holden; Frode Alfnes (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2020)
Agricultural technology change is required in developing countries to increase the robustness to climate-related variability, feed a growing population, and create opportunities for market-oriented production. This study investigates technological change in the form of adoption of improved wheat, drought-tolerant teff, and cash crops in the semi-arid Tigray region in northern Ethiopia. We analyze three rounds of panel data collected from smallholder farms in 2005/2006, 2009/2010 and 2014/2015 with a total sample of 1269 households. Double-hurdle models are used to assess how the likelihood (first hurdle) and intensity of technology adoption (second hurdle) are affected by demographic, weather, and market factors. The results indicate that few smallholders have adopted the new crops, those that have adopted the crops only plant small shares of their land with the new crops, and that there has been only a small increase in adoption over the ten-year period. Furthermore, we find that high population density is positively associated with the adoption of improved wheat, and previous period's rainfall is positively associated with the adoption of drought-tolerant teff. The adoption of cash crops is positively associated with landholding size and access to irrigation. The policy implications of these results are that the government should increase the improved wheat diffusion efforts in less population dense areas, make sure that drought-tolerant teff seed is available and affordable after droughts, and promote irrigation infrastructure for production of cash crops.
Keywords: O33; Q12; Q16; R34; 330; Semi-arid areas; climate risk; new crop varieties; double-hurdle; northern Ethiopia